Hazardous industrial waste treatment - Wang, Lawrence K; Hung, Yung-Tse; Lo, Howard H; Yapijakis, Constantine (CRC/Taylor & Francis, 2007)
1- Implementation of industrial ecology for industrial hazardous waste management, Lawrence K. Wang and Donald B. Aulenbach. 2- Bioassay of industrial waste pollutants, Svetlana Yu. Selivanovskaya, Venera Z. Latypova, Nadezda Yu. Stepanova, and Yung-Tse Hung. 3- In-plant management and disposal of industrial hazardous substances, Lawrence K. Wang. 4- On-site monitoring and analysis of industrial pollutants, Jerry R. Taricska, Yung-Tse Hung and Kathleen Hung Li. 5- Pollution prevention, J. Paul Chen, Thomas T. Shen, Yung-Tse Hung and Lawrence K. Wang. 6- Stormwater management and treatment, Constantine Yapojakis, Robert Leo Trotta, Chein-Chi Chang and Lawrence K. Wang. 7- Site remediation and groundwater decontamination, Lawrence K. Wang. 8- Treatment of metal finishing wastes, Olcay Tunay, Isik Kabdaslt and Yung-Tse Hung. 9- Treatment of photographic processing wastes, Thomas W. Bober, Dominick Vacco, Thomas J. Dagon and Hervey E. Fowler. 10- Treatment of timber industry wastes, Lawrence K. Wang. 11- Explosive waste treatment, J. Paul Chen, Shuaiwen Zou, Simo Olavi Pehkomen, Yung-Tse Hung and Lawrence K. Wang. 12- Treatment of landfill leachate, Michal Bodzek, Joanna Surmacz and Yung-Tse Hung.